Pengaruh Bahan Ajar Bermuatan Folklor (Cerita Rakyat) Angkola terhadap Menulis Cerita Rakyat Siswa Kelas X SMK Negeri 1 Batang Angkola - Daulay, Ismail Rahmad; Afifah, Nur; Aritonang, Devinna Riskiana (Islamic Education, 2022)
The learning process has one component that supports the success of the learning process, namely teaching materials. Teaching materials are also a set of learning tools or tools that contain learning materials, methods, boundaries, and ways of evaluating which are systematically designed and interesting in order to achieve the expected goals in achieving competencies or sub-competencies with all their complexity in the learning process. In addition, teaching materials can be said to be systematically compiled lecture materials or materials that educators and students or lecturers and students use in the learning process. The purpose of this study is to describe the influence of teaching materials containing folklore in Angkola on writing folklore of class X students of SMK Negeri 1 Batang Angkola. Research results an increase in the influence of the influence of Angkola's Folklore Teaching Materials on writing folklore for Class X Students of SMK Negeri 1 Batang Angkola. This can be seen in the hypothesis test carried out on the data found, where the hypothesis obtained the value of rxy (productmoment correlation correlation between variable X and variable Y) is 0.889 so that when compared with r table i.e. (0.669>0.45 then the hypothesis in this study is accepted.